2018
DOI: 10.1097/imi.0000000000000488
|View full text |Cite
|
Sign up to set email alerts
|

Closure of Large Percutaneous Femoral Venous access using a Modified “Figure-of-Eight” Suture

Abstract: Recent advances in different percutaneous treatments made insertion of large-caliber sheaths in the femoral veins more common. Venous punctures are historically managed by initial manual compression with subsequent application of a compression bandage and bed rest. We describe a modified “figure-of-eight” suture technique for minimizing the risk of accidental puncture of the vein while grabbing the subcutaneous tissue. We examined the safety and feasibility of this technique combined with early mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The technique is safe and feasible, with an overall success rate of 92%. There are a few reports of surgical suture hemostasis after the removal of femoral venous sheaths in children, and the overall success rate is 98.7% [4][5][6][7][8]. It has been demonstrated that 89.3% of children cease bleeding quickly after ligation, 10.7% of them managing to stop the ow within two minutes, which indicates that the technique is highly effective in achieving rapid hemostasis in this demographic and can signi cantly reduce the time spent in hospital [13].…”
Section: Discssionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique is safe and feasible, with an overall success rate of 92%. There are a few reports of surgical suture hemostasis after the removal of femoral venous sheaths in children, and the overall success rate is 98.7% [4][5][6][7][8]. It has been demonstrated that 89.3% of children cease bleeding quickly after ligation, 10.7% of them managing to stop the ow within two minutes, which indicates that the technique is highly effective in achieving rapid hemostasis in this demographic and can signi cantly reduce the time spent in hospital [13].…”
Section: Discssionmentioning
confidence: 99%
“…Wyss et al investigated 56 patients who had undergone mitral valve repair via a percutaneous femoral vein approach, and revealed that the use of a revised temporary Figure-of-Eight suture with light bandages and short bed rest time (2-4 hours) was a secure and economical hemostatic option for large femoral vein damage[4]. Multiple studies have con rmed that Figure-of-Eight suture technology can also effectively achieved femoral vein hemostatic in adult patients with atrial brillation treated by radiofrequency ablation, signi cantly reduced the risk of rebleeding, shortened bed rest time, and alleviated the discomfort of patients during the use of large-calib venous delivery sheaths[5][6][7].…”
mentioning
confidence: 99%